Financial Reporting Act (FRA), 2015: A Revolutionary Era for Ensuring Effective Capital Market and Economic Development in Bangladesh (Global Journal of Management and Business Research, 2016)
Financial Reporting Act (FRA), 2015 is an excellent initiative for ensuring transparency and accountability in accounting and auditing profession in Bangladesh. Auditing is the key pillar of public confidence in corporate governance and reporting and the part of an integrated financial reporting supply chain that includes financial managers, directors, accountants and regulators domestically and internationally. Like other countries of the world, corporate failures and scandals are a bit linked with the accounting profession associated companies in Bangladesh as a result the need for monitoring the auditing and accounting activities grows louder after the recent crisis in the capital market. This study has conducted a SWOT analysis on FRA, 2015.
Keywords: FRA; FRC; financial reporting; transparency and accountability; capital market and economic development